Strengthening digital citizenship behavior to reduce cyberbullying through learning outcome mediation - Yuniawati, Elisa Ika; Tiatri, Sri; Beng, Jap Tji (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
Internet use that does not pay attention to digital ethics can lead to an increase in negative online behaviors such as cyberbullying among students. Cyberbullying behavior as a negative online behavior has a very serious impact not only on individual psychology but also learning outcomes so that it requires strategies and programs that can be used to prevent and reduce these impacts. Digital Citizenship is a concept of positive behavior when using the internet that contains ethics, responsibility, and utilizing the internet appropriately. In addition to digital citizenship behavior, learning outcomes also play a role in reducing negative online cyberbullying behavior. This study aims to examine the role of digital citizenship behavior on negative online cyberbullying behavior with learning outcomes as a mediator. In this study using a quantitative approach, surveys were distributed to 353 participants consisting of grade 1 to 3 junior high school students aged 11 to 16 years with male and female gender at two public junior high schools in Bali. The results showed that there was a role of digital citizenship toward cyberbullying, but learning outcomes did not mediate the relationship between digital citizenship and cyberbullying.